2015
DOI: 10.1590/1678-775720150041
|View full text |Cite
|
Sign up to set email alerts
|

Marginal integrity of restorations produced with a model composite based on polyhedral oligomeric silsesquioxane (POSS)

Abstract: Marginal integrity is one of the most crucial aspects involved in the clinical longevity of resin composite restorations. Objective To analyze the marginal integrity of restorations produced with a model composite based on polyhedral oligomeric silsesquioxane (POSS).Material and Methods A base composite (B) was produced with an organic matrix with UDMA/TEGDMA and 70 wt.% of barium borosilicate glass particles. To produce the model composite, 25 wt.% of UDMA were replaced by POSS (P25). The composites P90 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…According to the established criteria (continuous margins, gaps), the SEM analysis of the restoration/dentin/cementum interfaces of the three groups is presented in the following figures (figs. [4][5][6][7][8][9] Group RD Below CEJ We calculated the mean and standard deviation to compare the materials used according to established criteria (continuous margins, presence of gaps). It was found that among the three materials used for RD, RSD, RI at both the dentin and the cementum, there are no significant differences (RD/d = 0.661, RSD/d = 0.755, RSD/ c = 0.942; RI/d = 0.739; RI/c = 0.985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the established criteria (continuous margins, gaps), the SEM analysis of the restoration/dentin/cementum interfaces of the three groups is presented in the following figures (figs. [4][5][6][7][8][9] Group RD Below CEJ We calculated the mean and standard deviation to compare the materials used according to established criteria (continuous margins, presence of gaps). It was found that among the three materials used for RD, RSD, RI at both the dentin and the cementum, there are no significant differences (RD/d = 0.661, RSD/d = 0.755, RSD/ c = 0.942; RI/d = 0.739; RI/c = 0.985).…”
Section: Resultsmentioning
confidence: 99%
“…Correa Netto et al [4] and Shim et al [5] reported in their studies that the success of direct and indirect restorations depends on several factors, one of the most important being marginal adaptation.…”
Section: Above Cejmentioning
confidence: 99%
“…This apparatus processes the images generated and performs the volume analysis simultaneously to the light-curing [33]. The accuracy of this instrument is 0.1% of volumetric alteration, considering specimens of approximately 15 µ L [34]. To measure the polymerization shrinkage, a small portion of the composite was manually shaped in a polytetrafluoroethylene die, 4.8 mm in diameter at its base and 1.3 mm in height, resulting in a spherical cap shape (Figure 2).…”
Section: Polymerization Shrinkage Measurementmentioning
confidence: 99%
“…This set-up was then placed in a support in front of the load device coupled to the recording camera of the equipment (Figure 3). All specimens were stored for 5 min before the first volume measurement in an attempt to eliminate the influence of the relaxation generated by the gravity [33,34]. The total theoretical volume of the composite was 12.91 mm 3 and it was calculated by the formula of the spherical cap volume: This set-up was then placed in a support in front of the load device coupled to the recording camera of the equipment (Figure 3).…”
Section: Polymerization Shrinkage Measurementmentioning
confidence: 99%
“…Traditionally used dental filling materials include dental amalgams, resin ionomers, composite resins and glass ionomers. Dental filling material selection is based on properties including viscosity, moldability and the ideal marginal integrity of the dental filling in the tooth [7]. Dental fillings are also chosen based on susceptibility to corrosion from pH, temperature, protein, saliva, oral health conditions, and diet [8].…”
Section: Traditional Dental Fillings -An Overviewmentioning
confidence: 99%